Microstructural and mechanical study of PCL coated Mg scaffolds. (December 2014) - Yazdimamaghani, M.; Razavi, M.; Vashaee, D.; Tayebi, L.
<x content-type="archive" xml:space="preserve">Abstract</x> In recent years, attention has been focused on the magnesium (Mg) as a promising material in biodegradable metallic scaffolds for bone tissue engineering. Since an orthopedic scaffold is supposed to repair and regenerate fractured bones, its mechanical integrity is vital throughout the healing process. In this study, a biocompatible polymeric layer made of polycaprolactone (PCL) in different concentrations of 3% w/v and 6% w/v was coated on the surface of Mg scaffolds. The structural characteristics and mechanical behaviour of the Mg scaffolds during the immersion in physiological saline solution (PSS) were investigated. According to our results, the PCL coating hindered the diminution of mechanical stability of scaffolds to provide adequate support for bone healing. Specifically, scaffold coated with 3% w/v and 6% w/v PCL demonstrated 24 and 100% improvement in the elastic modulus and 41 and 83% enhancement in compressive strength respectively, after 24 h immersion in PSS, compare to the uncoated scaffold. Thus, PCL coating of Mg scaffolds may be a promising approach in the development of mechanically stable bone scaffolds.